2021
DOI: 10.3389/fcell.2021.733354
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by TDO2-Augmented Fibroblasts Regulate Pro-inflammatory Response in Macrophages

Abstract: Extracellular vesicles (EVs) are secreted lipid bilayer vesicles that mediate cell to cell communication and are effectors of cell therapy. Previous work has shown that canonical Wnt signaling is necessary for cell and EV therapeutic potency. Tryptophan 2,3-dioxygenase (TDO2) is a target gene of canonical Wnt signaling. Augmenting TDO2 in therapeutically inert fibroblasts endows their EVs with immunomodulatory capacity including attenuating inflammatory signaling in macrophages. Transcriptomic analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
(40 reference statements)
3
9
0
Order By: Relevance
“…TDO2‐CCM or CCM from and HDFs (HDF‐CCM) were prepared using ultrafiltration (100 kDa cutoff). The presence of EVs in these CCM samples was confirmed in previous work including the presence of conserved EV markers and absence of cellular contamination (Peck et al., 2021 ). We used a well‐established mouse model of acute myocardial infarction (AMI; Figure 1a ).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…TDO2‐CCM or CCM from and HDFs (HDF‐CCM) were prepared using ultrafiltration (100 kDa cutoff). The presence of EVs in these CCM samples was confirmed in previous work including the presence of conserved EV markers and absence of cellular contamination (Peck et al., 2021 ). We used a well‐established mouse model of acute myocardial infarction (AMI; Figure 1a ).…”
Section: Resultssupporting
confidence: 81%
“…The work detailed here represents a continuation of this mechanistic elucidation. Building from previous findings that TDO2 is a major upregulated target of wnt/β-catenin, we demonstrate that augmenting TDO2 expression in dermal fibroblasts switches their phenotype from therapeutically inert to potently immunomodulatory (Peck et al, 2021). In an in vivo model of acute myocardial infarction, we confirmed that the secretome of TDO2-augmented EVs exerted therapeutic effects compared to the secretome of normal fibroblasts.…”
Section:  Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, among subjects with dysbiosis, TDO 2 is present in plasma nanovescicles, and its levels are higher after 60 days of Acronelle ® (Bromatech S.r.l., Milan, Italy) assumption (Figure 1). Very few studies to date have demonstrated the presence of TDO 2/IDO in EVs obtained from patients with dysbiosis or inflammatory diseases [57][58][59][60] and, to the best of our knowledge, changes of TDO 2 levels in plasmatic EVs before and after probiotics treatment have not been described previously. Our results indicate that by plasmatic EVs, the microbiota can drive signals to the brain by inducing the modulation of neurotransmitters and their receptors.…”
Section: Discussionmentioning
confidence: 74%